2020
DOI: 10.1002/hed.26461
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic tumor volume and total lesion glycolysis as prognostic factors in head and neck cancer: Systematic review and meta‐analysis

Abstract: The role of metabolic tumor volume (MTV) and total lesion glycolysis (TLG) in head and neck cancer (HNC) prognosis is not well established. We conducted a systematic review focusing on MTV and TLG measured by 18 F-FDG positron-emission tomography in HNC. Meta-analyses were developed, estimating hazard ratios (HRs) for overall survival (OS) and disease-free survival (DFS). Eighteen studies were found with a total of 1512 patients. MTVadjusted analysis had an HR of 4.65 (95% CI = 2.04-10.6) for DFS and 3.89 (95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 40 publications
2
21
0
1
Order By: Relevance
“…15 Thus, MTV and TLG are more comprehensive tools for tumour evaluation and have been shown to provide prognostic information in other cancers. [16][17][18][19] Further, by summing the MTV and TLG for all metabolically active tumours, we can calculate the total MTV (tMTV) and total TLG (tTLG) to gain knowledge about the patient's total tumour burden (disease burden). Some previous studies have shown the prognostic role of different clinical and histopathological parameters on overall survival (OS) in high-grade GEP NEN.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Thus, MTV and TLG are more comprehensive tools for tumour evaluation and have been shown to provide prognostic information in other cancers. [16][17][18][19] Further, by summing the MTV and TLG for all metabolically active tumours, we can calculate the total MTV (tMTV) and total TLG (tTLG) to gain knowledge about the patient's total tumour burden (disease burden). Some previous studies have shown the prognostic role of different clinical and histopathological parameters on overall survival (OS) in high-grade GEP NEN.…”
mentioning
confidence: 99%
“…Most studies included NEN of all grades, and the authors noted that most studies did not make a clear distinction between NET G3 and NEC. This review included 23 studies with a total of 1799 patients, and showed an adjusted hazard ratio (HR) = 3.16 for [ 18 F]FDG PET/CT as prognostic for OS 22 .…”
mentioning
confidence: 99%
“…[ 10 ] The present results that demonstrate a significant association between higher TLG and shorter survivals (OS and DMFS) are in agreement with these previous results. [ 2 4 , 10 , 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Then, there are a wide variety of genes and enzymes involved in glycolysis [ 29 ]. Researchers have also screened different genes and key enzymes in the glycolysis process through different research methods to predict prognostic conditions [ 30 ]. Regrettably, there is still no gold standard for a good prognosis in the process of glycolysis.…”
Section: Discussionmentioning
confidence: 99%